On Normalisation Performance Scores Models: An Illustrative Case Study (Global Journal of Management and Business Research, 2018)
Problem Statement: Performance Management System (PMS) applies to all companies. It is a system that has been in existence for decades and, yet Human Resources professionals and managers have the difficult task of ensuring that it produces results intended for. One of the limitations currently is that models used to measure performance are subjective and methodologies such as normalization of performance scores are not applied consistently nor have some limitations. Methodology: This study design was a retrospective case study on a one-year performance review data. The hypothesis in the current study was that the modified normalization performance scores models reduces bias and performs better than the normalization score models. Final year-end performance scores for individual employees were used to assess four models. Results: The results showed no significant differences between the four models. Therefore, the modifying normalization performance scores did not improve the model. These results also revealed precincts of forced distribution such as the size of the business unit or organization and lastly, the employee-supervisor consequence. Recommendations/Value: Alternative approaches other than normalization of performance scores need to be considered in measuring performance. These methods need to adjust for factors such as the supervisor or manager influence, the complexity of the job, the variations in the job functions and the business unit size.
Keywords: performance management; management education; normalization; business management and research